Representações sociais no ensino de ciências por professores da educação básica - Santos, Neuza Batista dos (2011)
Social representations in Science teaching by primary school teachers from the Education Nucleus of Maringá, Maringá PR Brazil, are investigated. Research aims comprised a) identification of social representations of teaching Science within teachers? discourse; b) pinpointing their consequences in the teaching of Science. Qualitative approach employed a half-structured interview and the subjects were 24 Primary School teachers who have a degree in Science and taught Science. Discourse on the teaching of Science was analyzed by Moscovici?s (2009) Theory of Social Representations through Bardin?s (1977) contents analysis. Research results show that teachers are concerned with contents found in the textbook, students? daily life, news broadcasted by the media, and not necessarily understood as linked to the scientific field. The above practice materializes planning rather than the students? whole formation. Teaching is highly traditional, with scanty criticism, no deepening of basic knowledge, without any spirit of discovery or any debates for more citizenship awareness. Interviewed teachers failed to indicate important and decisive knowledge for the students? scientific formation. In fact, they are more tuned to the school organization?s point of view than with the teaching of Science. This type of teaching does not have any commitment with going beyond initial or ingenuous Science representations. Research suggests that changes in SR requires a) another type of Science teacher profile (open to new methods; researchers); b) an understanding of what may be done in the classroom with regard to teaching methodology in Science, Discourse and Interactive Education from the point of view of knowledge items and psychosocial mechanism; c) an awareness that the tradition school organization model is not the only resource that teachers have to teach Science.